PENGUKURAN KUALITAS AUDIT : ETIKA, INDEPENDENSI, DAN KOMPETENSI AUDITOR - Kinasih, Nastiti Pramesti; Widyaningsih, Aristanti; Heryana, Tony (Universitas Boyolali, 2023)
The study of audit quality and the impact of auditor ethics, auditor independence, and auditor competence is a compelling topic for research investigations. This research aims to explore the portrayal and viewpoints regarding ethics, independence, and auditor competence, and how they affect audit quality, drawing from literature reviews and prior research. Audit quality is how an auditor assesses a company from its financial reports and accounting system and looks at possible violations committed by entities in its financial reports and accounting system. Auditor ethics, namely how auditors need to comply with the rules for ethical behavior stated in the public accountant's code of ethics. Independence is when an auditor has no conflict of interest with clients or other parties who have personal interests. Competency is the knowledge, experience and special skills that an auditor has in accordance with his profession. Ethics, independence and auditor competence have a major influence on audit quality assessment. When an auditor fulfills these three elements, the resulting audit quality will be better and gain full trust from the public and interested parties.